A Content analysis of the 2023 Israel-Palestine conflict news reporting in The Star Online, Malaysia - Lim, Lai Hoon (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Israel-Palestine conflict is a complex geopolitical struggle which captivated media attention worldwide. On 7th October 2023, Hamas militants initiated a momentous attack on Israel from the Gaza Strip, resulting in the tragic loss of over 1,400 lives and the capture of more than 200 individuals. In response to these hostilities, Israel has launched counterattacks on Gaza, which brought the unfortunate losses of more than 10,000 people. The news coverage of this conflict revealed the multifaceted dimensions of the struggle between the two countries, stemming from historical, geographical, and political disparities. The media’s portrayal of the conflict significantly influences public perception and policy decisions. This study analyses how The Star Online, a prominent Malaysian news outlet, frames the Israel-Palestine conflict. Using a mixed-methods approach, this study employs both quantitative and qualitative content analyses. Keyword searches, including “Israel-Palestine conflict” and “Gaza War”, were conducted to gather relevant news articles from 7th October 2023, to 7th January 2024. The aim is to identify prevailing topics and sources that subsequently help reveal the media treatment frameworks in this event. Examining these frameworks sheds light on how media representations shape the audience’s understanding of the conflict and its implications for regional stability. Both thematic and episodic frames are found in the findings where the thematic frames appear dominant. Solving the conflict is assigned as a societal responsibility. The frames proposed solutions and consequences of the conflict despite the conflict’s root causes are not discussed.